Diversity and structure of the gallery forest of the Fuerte river, Sinaloa, Mexico: Diversidad del Bosque del río Fuerte - Sampayo-Maldonado, Salvador; Moreno-Aldaco , Julián Darío; Lara-Ponce, Estuardo; Piña-Ruíz, Hugo Humberto (Ecosistemas y Recursos Agropecuarios, 2021)
The Fuerte River is the most important hydrological current in northern Sinaloa, its biological wealth is part of the biocultural heritage of the Yoreme-Mayo people and is essential for their well-being. However, pollution, fragmentation and loss of biodiversity are negatively impacting its functionality. Therefore, the objective was to evaluate and describe the diversity and structure of the vegetation associated with the gallery forest of the Fuerte river. 41 circular plots of 0.1 ha were established, in which dasometric data (height, normal diameter and crown coverage) were taken. The structure was characterized by diameter distribution and height, using the importance value index. Diversity was evaluated with the Equity (E), Margalef (DMg), Simpson (D) and Shannon-Wiener (H’) indices. 27 species were recorded of which 16 are native. The Fabaceae family was the most represented with 11 species, followed by Salicaceae with two. The arboreal stratum had an importance value of 79.18%, and 14.11% for the shrub. 60% of the trees were grouped in the diameter category of 5 and 74% in the categories of 5 and 10 in height. The most ecologically important species for the riparian ecosystem were Populus mexicana, Pithecellobium dulce and Prosopis juliflora. The Fuerte river presented a high diversity with dominance of the arboreal stratum and a population with a youthful structure, characteristic of an ecosystem with the presence of disturbances due to human activities.